Purple sweet potato anthocyanin attenuates fat-induced mortality in Drosophila melanogaster. - Wang, L.; Li, Y.M.; Lei, L.; Liu, Y.; Wang, X.; Ma, K.Y.; Zhang, C.; Zhu, H.; Zhao, Y.; Chen, Z.Y. (Experimental Gerontology, 2016)
A high fat diet induces the accumulation of lipid hydroperoxides (LPO), accelerates the ageing process and causes a greater mortality in Drosophila melanogaster. Purple sweet potato is rich in antioxidant anthocyanin. The purpose of the present study was to examine if supplementation of purple sweet potato anthocyanin (PSPA) could reduce the mortality of fruit flies fed a high-fat diet. Results showed that the mean lifespan of fruit flies was shortened from 56 to 35days in a dose-dependent manner when lard in the diet increased from 0% to 20%. PSPA supplementation partially attenuated the lard-induced mortality. The maximum lifespan and 50% survival time were 49 and 27days, respectively, for the 10% lard control flies, in contrast, these parameters increased to 57 and 30days in the PSPA-supplemented fruit flies. Similarly, addition of lard into diet increased the total body LPO, while addition of PSPA partially attenuated its increase. Real-time PCR analysis indicated that PSPA-supplemented diet significantly up-regulated the mRNA of superoxide dismutase (SOD), catalase (CAT) and Rpn11, compared with the control lard diet. The western blot analysis also demonstrated that PSPA supplementation was associated with up-regulation protein mass of SOD1, SOD2, and CAT. In addition, PSPA supplementation could restore the climbing ability of fruit flies fed a 10% lard diet. We could conclude that the lifespan-prolonging activity of PSPA was potentially mediated by modulating the genes of SOD, CAT and Rpn11.